Proximal Humerus Fracture-Dislocation with Laceration of the Axillary Artery: A Case Report - Cotman, Steven J. (Iowa Orthop J, 2017)
BACKGROUND: Proximal humerus fractures account for approximately 4-6% of all fractures. While the majority of these fractures are treated non-operatively, the amount of fracture displacement, concomitant injuries, and patient factors often result in the need for surgical stabilization. Although concomitant neurovascular injury in the setting of low-energy trauma is rare, injury to the surrounding neurovascular structures have previously been reported. METHODS: We report a case of a 79-year-old male who sustained a low energy fall resulting in a two-part fracture dislocation of the proximal humerus with an associated brachial plexopathy and axillary artery laceration. The patient underwent emergent open reduction internal fixation of his fracture in addition to an axillary-brachial artery bypass using a reverse-saphenous vein graft. The current article reports the presentation, management and prognosis of this rare injury. RESULTS: At 6 months, the patient demonstrated limited active shoulder abduction with no observed motor function at this elbow, wrist or hand. Radiographic follow up demonstrated a reduced glenohumeral joint with evidence avascular necrosis of the humeral head. CONCLUSION: Fracture-dislocations of the proximal humerus may be associated with significant neurovascular injury in the setting of low energy trauma. Despite early treatment, the prognosis of patients with this constellation of injuries is guarded.